1995
DOI: 10.1042/bj3110283
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration by pulsed neutron scattering that the arrangement of the Fab and Fc fragments in the overall structures of bovine IgG1 and IgG2 in solution is similar

Abstract: The bovine IgG1 and IgG2 isotypes exhibit large differences in effector functions. To examine the structural basis for this, the 12-domain structures of IgG1 and IgG2 were investigated by pulsed neutron scattering using a recently developed camera LOQ. This method reports on the average relative disposition in solution of the Fab and Fc fragments in IgG. The radii of gyration (RG) were found to be similar at 5.64 and 5.71 nm for IgG1 and IgG2 respectively in 100% 2H2O buffers. The two cross-sectional radii of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…The derived step length range of 17.5 nm is consistent with Guinier analysis of IgG by Mayans et al 18 ;…”
Section: Sensiq Propagating Plasmon Surfacesupporting
confidence: 89%
“…The derived step length range of 17.5 nm is consistent with Guinier analysis of IgG by Mayans et al 18 ;…”
Section: Sensiq Propagating Plasmon Surfacesupporting
confidence: 89%
“…Serum albumin is reported to be an oblate ellipsoid with dimensions of 14 nm  4 nm (Bendedouch and Chen, 1983). IgG is reported to have a cross-sectional diameter of 4.8 AE 0.3 nm (Mayans et al, 1995). In both cases, one dimension of the protein is similar in size to the estimated interchain distances reported in Table II.…”
Section: Dynamic Binding Capacity Of Iggmentioning
confidence: 78%
“…Ultimately the combination of the scattering curves in Figs. 1-3 with a recently-developed method of automated curve fitting of domain models to the scattering curves (which is constrained using known atomic structures for individual domains [22,24]) should permit the quantitative testing of sterically-allowed domain structures in FVIIa, sTF and their complex to produce improved low-resolution structures compared to those presented in Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the average of the X-ray and neutron values will approximately represent a structure at infinite contrast by analogy with the Stuhrmann relationship, in which this contrast effect is minimised [9,10,25]. As the neutron intensities had been standardized using a deuterated polymer standard [23], for recombinant human IgE-Fc (Mr of 75,300) [22] and 0.181 for bovine IgG1 and IgG2 (Mr of 144,000) [24]. It is concluded that the complex was formed as expected.…”
Section: Neutron Data On Factor Vlla Extraeellular Tissue Factor Andmentioning
confidence: 99%